2021
DOI: 10.1021/acs.langmuir.1c01607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elasticity of Silica Capsules on Cellular Uptake

Abstract: Understanding the impact of the physicochemical properties of nanoparticles (NPs) on cellular uptake is important to design optimal drug-delivery nanocarriers. Therein, the influence of NP elasticity on bio-nano-interactions remains elusive due to the complexity of factors affecting cellular uptake. Herein, we synthesized SiO 2 capsules with tunable elasticity using metal−organic frameworks as templates to investigate their interactions with cells. Young's moduli of the resultant water-filled SiO 2 capsules wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The stiffness is controlled via the variation of capsule shell thickness. 168 Increasing the stiffness of silica nanoparticles results in higher cellular uptake in both HeLa cells and macrophage RAW264.7, 9 times and 1.3 times more than soft nanoparticles, respectively. The uptake of stiff nanoparticles was mainly via clathrin-mediated endocytosis whereas the soft silica nanoparticles entered the cells mainly via caveolae-dependent endocytosis.…”
Section: The Stiffness Of Nanoparticlesmentioning
confidence: 98%
See 1 more Smart Citation
“…The stiffness is controlled via the variation of capsule shell thickness. 168 Increasing the stiffness of silica nanoparticles results in higher cellular uptake in both HeLa cells and macrophage RAW264.7, 9 times and 1.3 times more than soft nanoparticles, respectively. The uptake of stiff nanoparticles was mainly via clathrin-mediated endocytosis whereas the soft silica nanoparticles entered the cells mainly via caveolae-dependent endocytosis.…”
Section: The Stiffness Of Nanoparticlesmentioning
confidence: 98%
“…167 The stiffness of nanoparticles has an impact on the endocytosis in cancer and healthy cells. 135,168 Ma et al synthesized silica capsules with identical size, shape, composition, and surface charge (B200 nm, spherical shape) but different stiffness from 3.8 MPa to 4.7 GPa. The stiffness is controlled via the variation of capsule shell thickness.…”
Section: The Stiffness Of Nanoparticlesmentioning
confidence: 99%
“…The advantages of soft nanoparticles have been contested by other reports. In a recent study on the role of elasticity in the uptake of silicon oxide nanocapsules by HeLa cells, the authors reported that increased elasticity resulted in higher cellular uptake of stiff SiO 2 nanocapsules by about nine-fold compared to soft nanocapsules [63]. Mechanistic investigation showed that hard nanocapsules were internalized via clathrin mediated endocytosis, while soft nanocapsules were taken up by either the caveolae dependent pathway or via micropinocytosis, as observed in soft nanoparticles with extremely low elastic modulus [60,64].…”
Section: Elasticitymentioning
confidence: 99%
“…For cell internalization, the consensus opinion is that stiff CPs can induce higher endocytosis compared to soft CPs, which has been proven by using different CPs (e.g., polymer micelles, microgels, silica capsules, and liposomes) on various cell lines (e.g., A375, HeLa, MCF-7, and MDA-MB-231 cells). ,,,, Molecular dynamics simulations demonstrated that soft CPs underwent significant deformation during the internalization and more binding energy was required to overcome the bending energy to complete the cell internalization . Although soft CPs decrease the tumor cell endocytosis from in vitro experiments, they can improve the circulation time and biodistribution more than stiff CPs, which is more important to reduce the side effect and enhance the drug delivery efficacy …”
Section: Influence Of Stiffness On Drug and Vaccine Deliverymentioning
confidence: 99%